Upsa centennial, a new genus and species (Coleoptera: Scarabaeidae: Scarabaeinae: Endroedyolini) from the Southern Mistbelt forest in South Africa: celebrating 100 years of entomology at the University of Pretoria - Deschodt, Christian M.; Sole, Catherine L.; Scholtz, Clarke H. (Zootaxa, 2020)
Upsa centennial Deschodt, Sole & Scholtz, new genus and species is described, celebrating a century of entomology at the University of Pretoria. This new genus in the dung beetle tribe Endroedyolini (Scarabaeidae: Scarabaeinae) occurs in the Albany Coastal Mistbelt forest in the Eastern Cape Province in South Africa. A distribution map and key for all genera and species in the tribe are provided.[Genus Zoobank url: urn:lsid:zoobank.org:act:92A64613-A8CE-48DF-84D9-7450EA1D40AA]